The management of intellectual property - Bosworth, Derek L.; Webster, Elizabeth (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
This book brings together innovative contributions on the management of intellectual property (IP) and intellectual property rights by an esteemed and multi-disciplinary group of economists, management scientists, accountants and lawyers.
Includes bibliographical references and index.
lje 23/08/16
Loan
Keywords: Intellectual property; Intangible property; Technological innovations